Pharmacoepidemiology and clinical characteristics of medication-related osteonecrosis of the jaw - Hyo-Jeong Son; Jin-Woo Kim; Sun-Jong Kim (SpringerOpen, 2019)
Abstract Background The aim of this study was to investigate clinical and pharmacoepidemiologic characteristics of medication-related osteonecrosis of the jaw. Methods The study population is comprised of 86patients who were diagnosed with ONJ at Ewha Womans University Mokdong Hospital from 2008 to 2015. Factors for epidemiologic evaluation were gender, age, location of lesion, and clinical history. The types of bisphosphonates, duration of intake, and the amount of accumulated dose were evaluated for therapeutic response. Clinical symptoms and radiographic images were utilized for the assessment of prognosis. Results Among the 86 patients, five were male, whereas 81 were female with mean age of 73.98 (range 45-97). Location of the lesion was in the mandible for 58 patients and maxilla in 25 patients. Three patients had both mandible and maxilla affected. This shows that the mandible is more prone to the formation of ONJ lesions compared to the maxilla. ONJ occurred in 38 cases after extraction, nine cases after implant surgery, six cases were denture use, and spontaneously in 33 cases. Seventy-six patients were taking other drugs aside from drugs indicated for osteoporosis. Most of these patients were diagnosed as osteoporosis, rheumatic arthritis, multiple myeloma, or had a history of cancer therapy. Higher weighted total accumulation doses were significantly associated with poorer prognosis (P < 0.05). Conclusion Dose, duration, route, and relative potency of bisphosphonates are significantly associated with treatment prognosis of osteonecrosis of the jaw.